2004
DOI: 10.1063/1.1640462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrinsic stress on preferred orientation in AlN thin films

Abstract: Articles you may be interested inSynthesis and characterization of 10nm thick piezoelectric AlN films with high c-axis orientation for miniaturized nanoelectromechanical devices Appl. Phys. Lett. Epitaxial growth and orientation of AlN thin films on Si(001) substrates deposited by reactive magnetron sputteringWe examine the effect of ion impact energy on the intrinsic stress and microstructure of aluminum nitride thin films deposited using a filtered cathodic arc. The dependence of intrinsic stress on ion impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…demonstrated that TiC/a:C coatings prepared using a pulsed closed field unbalanced magnetron sputtering system showed high hardness (24)(25)(26)(27)(28)(29), low COF (0.24-0.25) and low wear rate (less than 2.5×10 −7 mm 3 /Nm) when the C concentration is in the range of 55-66 at.%. And Wilhelmsson et al [14] put forward a new design of low-friction nanocomposite carbide film succeeded in decreasing COF…”
Section: Introductionmentioning
confidence: 98%
“…demonstrated that TiC/a:C coatings prepared using a pulsed closed field unbalanced magnetron sputtering system showed high hardness (24)(25)(26)(27)(28)(29), low COF (0.24-0.25) and low wear rate (less than 2.5×10 −7 mm 3 /Nm) when the C concentration is in the range of 55-66 at.%. And Wilhelmsson et al [14] put forward a new design of low-friction nanocomposite carbide film succeeded in decreasing COF…”
Section: Introductionmentioning
confidence: 98%
“…This, coupled with the anisotropic elastic modulus of the HA crystals, may result in textured polycrystalline configurations that minimize strain energy. Texture formation has been observed in other hexagonal ceramics deposited under anisotropic stress conditions and may be one of the main routes for strain energy relaxation [39]. Since our HA coatings exhibit no residual stress after deposition, as indicated by no detectable changes in peak position and width in XRD scans, it is essential to estimate the magnitude of stresses that may have been present during deposition.…”
Section: Stress-induced Ha Texture and Ttcp Formationmentioning
confidence: 99%
“…Changes in the preferred orientation of crystallites correlated with the relief of stress were also more recently observed for aluminium nitride (AlN) films deposited using a cathodic arc with PIII [13]. The highest stress obtained was around 4 GPa using a DC bias of 200 V with no PIII pulsed bias applied.…”
Section: Effects On Microstructure and Preferred Orientationmentioning
confidence: 71%